Implementasi Struktur Data Dictionary Untuk Sistem Monitoring Perangkat Internet Of Things - Galeh Prehandayana; Widhi Yahya; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Development of internet has been increased in recent years. One of the well developed internet technology is called Internet of things (IoT). IoT is able to transmit data through the network without direct interaction of person-to person or person-to-computer. The increase in size and amount of IoT environments complemented with the complex usage oftenly cause disturbances on networks and devices. Well developed device management is required to observe and availability of networks to prevent disturbances. Microcomputers with Raspberry Pi is required to develop the system. The device monitoring system of IoT works on transport layer using UDP protocol, the system will take only the required data for effective computing. Data structure will be designed with Dictionary Data Structure system, the monitoring system of IoT then developed by modifying the Management Information Base (MIB). The development of agent and manager will be adjusted according to MIB on SNMP with OID categories to create a well structured information and data to create an accurate interface for device monitoring. The result of IoT device monitoring is processed from data package on one transmission with the size of 402 bytes, slighty different with previous research which is 326 bytes, the result is caused by the usage of dictionary data structure which key and value can choose data based on OID category. The IoT device monitoring system is more effective than 3916 bytes SNMP protocol.